2020
DOI: 10.1038/s41598-020-67285-y
|View full text |Cite
|
Sign up to set email alerts
|

The Geriatric Nutritional Risk Index predicts postoperative complications and prognosis in elderly patients with colorectal cancer after curative surgery

Abstract: Malnutrition has been considered to be associated with the prognosis of cancer. the Geriatric nutritional Risk index (GnRi), based on serum albumin levels, present body weight, and ideal body weight, is a simple screening tool to predict the risk of nutrition-related morbidity and mortality in elderly patients. We aimed to evaluate whether preoperative GnRi was associated with postoperative complications and prognosis in elderly patients with colorectal cancer (cRc). We retrospectively enrolled 313 CRC patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 56 publications
5
88
0
Order By: Relevance
“…Seven of the studies lacked relevant outcomes. Therefore, our meta-analysis included nine studies involving 2,153 patients [ 10 , 12 , 14 , 19 24 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven of the studies lacked relevant outcomes. Therefore, our meta-analysis included nine studies involving 2,153 patients [ 10 , 12 , 14 , 19 24 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies were from Japan, and two studies were from China. Two studies reported GC [ 19 , 22 ], three studies reported ESCC [ 14 , 20 , 21 ], two studies reported CRC [ 10 , 12 ], one study reported colorectal liver metastasis (CRLM) [ 24 ], and one study reported pancreatic ductal adenocarcinoma (PDAC). In addition, four studies reported postoperative complications, eight studies reported OS, two studies reported RFS, and two studies reported DFS and CSS, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been reported that a nomogram may be effective in preventing complications. [28,29] In addition, the nomogram may be bene cial for counseling patients. Therefore, we expect that our nomogram can play an important role for LARS therapy.…”
Section: Discussionmentioning
confidence: 99%